Acute hematological, metabolic, and inflammatory responses to simulated-6000 ft masked versus unmasked high-intensity interval training in youth soccer players: a randomized crossover pilot study - Akol, T.; Yapici, A.; Ergin, G. F.; Atabas, E. G. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background High-intensity interval training (HIIT) with respiratory-restricting masks is used to simulate hypoxic training and potentially enhance physiological adaptations. However, the acute hematological, metabolic, and inflammatory responses to masked versus unmasked HIIT in youth soccer players remain unclear. This study aimed to compare these responses during simulated 6000-ft masked and unmasked HIIT.